Real-world insights into moderately hypofractionated thoracic radiotherapy in elderly and multimorbid patients with stage II/III NSCLC: a retrospective study - Helene Kravutske; Sina Mansoorian; Lukas Käsmann; Janina Lehmann; Cedric Richlitzki; Diego Kauffmann-Guerrero; Nina-Sophie Schmidt-Hegemann; Niels Reinmuth; Amanda Tufman; Julien Dinkel; Richard Gaus; Farkhad Manapov; et al. (Acta Oncologica, 2025)
Purpose: Investigating real-world outcomes of moderately hypofractionated radiotherapy (hypoRT) in elderly and multimorbid stage IIB–IIIC non-small-cell lung cancer (NSCLC) patients ineligible for concurrent chemoradiation.